Anatomical berry characteristics during the development of grape berries with different shapes - Chuan Zhang; Xiucai Fan; Chonghuai Liu; Jinggui Fang (Horticultural Plant Journal, 2021)
The aim of this study was to characterize the changes in berry anatomy during the development of grape (Vitis vinifera L., and Vitis vinifera × Vitis labrusca) with different shapes. Paraffin sectioning was used to examine the structural parameters of the cells. The results revealed that, with the development of berries, the transverse and longitudinal diameters of the flesh cells gradually increased, revealing certain regularity. However, the transverse and longitudinal diameters of the epidermal and sub-epidermal cells were different between varieties, reflecting the specificity of the varieties. The growth of the transverse and longitudinal diameters of the berries was found to be completed in the early stage of development. A combination of correlation analysis and size analysis for each cell layer revealed that, due to the small cross-sectional area of the epidermal and sub-epidermal cells, the influence of these cells on the transverse and the longitudinal diameters of the berries would be small. In conclusion, the longitudinal and transverse diameters of the grape berries were mainly determined by the longitudinal and transverse diameters of the flesh cells. The different shapes of the grape berries could mainly be attributed to the different growth rates of the flesh cells in the longitudinal and transverse directions. These different rates of growth led to different lengths and widths of the berry.